THE MODEL OF SUSTAINABLE DEVELOPMENT AS AN ECONOMIC CATEGORY - SHMORHUN, Yevheniia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the essence of the concept of "sustainable development model", analyzed the components of the sustainable development model. The article substantiates the similarity of existing approaches of various authors to the introduction of sustainable development. The principles of the model of sustainable development are disclosed. The article also provides the genesis of the economic category "model of sustainable development".Ensuring sustainable socio-economic development has been one of the most important problems for many years not only for individual enterprises, but also for the national economy as a whole. The category "model of sustainable development" is multifaceted and complex, so many questions remain undefined and require further research. As of today, there are various methods for defining the phenomenon of the model of sustainable development and interpreting its features, mechanisms of support. Based on the analysis of literary sources, the author believes that the model of sustainable development is a complex category that involves a formalized description and/or quantitative expression of the final results of social, economic and environmental components of entrepreneurial activity with the aim of improving the quality of life of people.The author comes to the conclusion that the concept of sustainable development is more often used to determine the growth indicators of the country's economy, regions, individual branches of industry or enterprises. At the same time, in our opinion, insufficient attention is paid to the social part of sustainable development, which indicates insufficient understanding of the true essence of this concept, namely the balance of all its components.
Keywords: sustainable development; model of sustainable development; harmonious development; growth; development